Lectins. Methods and protocols (Springer Nature, 2014)
Lectins: Methods and Protocols summarizes classic lectin technologies and advanced techniques with high throughputs and sensitivities. Chapters include methods and techniques for serial lectin-affinity chromatography procedure, lectin-probed western blot and histochemical analyses, quantitative interaction analyses based on equilibrium dialysis, isothermal calorimetry, surface plasmon resonance, techniques for elucidating functions of endogenous animal lectins, advanced methods on "engineer" novel lectins by evolutionary concepts, and special equipment. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Lectins: Methods and Protocols seeks to aid not only lectin specialists but also non-experts including both young scientists.
FP7 Ideas: European Research Council
English
Keywords: Proteins; lectin technologies; lectin-probed western blot; lectins; serial lectin-affinity chromatography